SURG-24. QUANTITATIVE ANALYSIS OF TUMOR CELL DENSITY AND PROTOPORPHYRIN IX FLOURESCENCE IN GLIOMA PATIENTS USING PAIRED STIMULATED RAMAN HISTOLOGY AND TWO-PHOTON EXCITATION FLUORESCENCE MICROSCOPY. (14th November 2022) - Nasir-Moin, Mustafa; Wadiura, Lisa Irina; Juros, Devin; Movahed-Ezazi, Misha; Lee, Matthew; Weiss, Hannah; Müther, Michael; Alber, Daniel; Ratna, Sujay; Fang, Camila; Suero-Molina, Eric; Hellwig, Sönke; et al.
Abstract: Fluorescence guidance is widely utilized to improve the precision of cancer surgery. 5-aminolevulinic acid, the most widely used fluorophore in glioma surgery, is thought to cause selective accumulation of fluorescent protoporphyrin IX (PpIX) in tumor cells by exploiting pathologic alterations in heme biosynthetic pathways. PpIX-induced fluorescence is highly specific for densely tumor-infiltrated tissue but less effective for visualizing the tumor periphery. To improve clinical detection of PpIX, we developed a microscope to perform paired stimulated Raman histology and two-photon excitation fluorescence microscopy (TPEF) and validated it in 175 fresh, unprocessed core tumor specimens from 75 high-grade glioma patients and three central nervous system lymphoma patients across three institutions. Surprisingly, intracellular PpIX accumulation was observed primarily in cells with histiocytic, rather than neoplastic morphology, and the number of cells concentrating PpIX within the cytoplasm was associated with the abundance of CD163 positive cells (p< 0.02). There was no correlation between the degree of tumor cellularity and the concentration of PpIX across all imaged specimens (R=-0.21). Our findings encourage reconsideration of the existing theory of 5-ALA-induced tumor cell fluorescence in gliomas and demonstrate how 5-ALA and TPEF imaging can provide a window into the immune microenvironment of human gliomas.